Gastrojejunal Anastomotic Technique. Does It Matter? Weight Loss and Weight Regain 5 Years After Laparoscopic Roux-en-Y Gastric Bypass - Fehervari, Matyas (Obes Surg, 2020)
PURPOSE: The gastrojejunostomy during laparoscopic Roux-en-Y gastric bypass (LRYGB) can be constructed by hand sewn (HSA), linear (LSA) and circular (CSA) stapler technique. They are all considered safe; however, it is not known which the best technique is. Short-term follow-up suggest no difference in weight loss or weight regain between them. However, there is no information on these parameters in the long term. Theatre time and cost are other important factors defining the best way to form gastrojejunostomy. MATERIALS AND METHODS: In a prospective longitudinal cohort study consecutive patients following primary LRYGB were recruited to a bariatric database in a tertiary care centre. Anastomotic technique, diameter, the length of operations and associated costs, weight loss and weight regain were recorded. Patients were followed up for 5 years. RESULTS: A total of 385 patients with an initial body mass index of 47.1 kg/m(2) (35–68) were enrolled to this study. This decreased to 33.3 kg/m(2) (21–54 kg/m(2)) after 5 years. There was no difference in %TWL after 3 years, P = 0.296, or 5 years, P = 0.187, between the techniques. The number of patients with weight regain was not different after 3 years, P = 0.224, or 5 years, P = 0.795. All techniques had similar operative time. CSA has a higher material cost. Early anastomotic stricture was more common following HSA; however, the difference was not significant. CONCLUSION: Mid-term weight loss and weight regain are not related to anastomotic technique, and there is no difference in operative time associated to them. Circular stapler technique has a higher material cost due to the additional stapler.